Andrés PÉREZ-SIMÓN, ed. y trad., "Despistemes: la teoría literaria y cultural de Emil Volek (antología de textos)". Madrid, Verbum, 2018, 383 pp. - Estrada Orozco, Luis Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Review of Despistemes: la teoría literaria y cultural de Emil Volek (antología de textos), book edited and translated by Andrés Pérez-Simón, Ph.D. Dr. Pérez-Simón selects fifteen essays by Czech professor Emil Volek. The book includes seven essays translated into Spanish for the first time as well as an unpublished essay. The volume offers the Spanish language reader an approach to professor Volek’s research interests through a selection of his work as a scholar and a critic of Latin American literature and culture, and of literary and cultural theories in U.S. academia.